Enhanced ant-based routing for improving performance of wireless sensor network - Abdul Nasir, Husna Jamal; Ku-Mahamud, Ku Ruhana; Kamioka, Eiji (Institute of IInstituteof IInformation Technology, Kohat University of Science and Technologynformation Technology, Kohat University of Science and Technology, 2017)
Routing packets from the source node to the destination node in wireless sensor network is complicated due to the distributed and heterogeneous nature of sensor nodes. An ant colony system algorithm for packet routing in WSN that focuses on a pheromone update technique is proposed in this paper. The proposed algorithm will determine the best path to be used in the submission of packets while considering the capacity of each sensor node such as the remaining energy and distance to the destination node. Global pheromone update and local pheromone update are used in the proposed algorithm with the aim to distribute the packets fairly and to prevent the energy depletion of the sensor nodes. Performance of the proposed algorithm has outperformed five (5) other common algorithms in static WSN environment in terms of throughput, success rate, packet loss rate, energy consumption and energy efficiency. Overall, the proposed algorithm can lead to reduction of packet loss rate during packet routing and increase of network lifetime.